Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA): Environmental and Social Management Plan (ESMP) for Pilot of Climate Smart Agricultural Innovations and Climate Information Service Technologies in Ethiopia - International Maize and Wheat Improvement Center; Ethiopian Institute of Agricultural Research (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The environmental and social screening exercise conducted on proposed CSA demonstration plots confirmed a range of Environmental and Social (E&S) risks, which if not mitigated, could cause harm to people and the environment. Based on these findings, this ESMP is prepared to clarify (i) the measures that will be taken during the implementation of project activities to eliminate or offset adverse E&S impacts, or to reduce them to acceptable levels; and (ii) actions needed to implement these measures.